2017
DOI: 10.1097/ta.0000000000001324
|View full text |Cite
|
Sign up to set email alerts
|

Preperitoneal pelvic packing reduces mortality in patients with life-threatening hemorrhage due to unstable pelvic fractures

Abstract: Background A 2015 AAST trial reported a 32% mortality for pelvic fracture patients in shock. Angioembolization (AE) is the most common intervention; the Maryland group revealed time to AE averaged 5 hours. The goal of this study was to evaluate the time to intervention and outcomes of an alternative approach for pelvic hemorrhage. We hypothesized preperitoneal pelvic packing (PPP) results in a shorter time to intervention and lower mortality. Methods In 2004 we initiated a PPP protocol for pelvic fracture he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
147
1
20

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(176 citation statements)
references
References 31 publications
8
147
1
20
Order By: Relevance
“…A recent multicenter prospective observational study of 1,339 patients with pelvic fracture found that angioembolization and external pelvic fixation were the most common hemorrhage control techniques for arterial and venous bleeding respectively. 25 Whereas the subgroup with hemorrhagic shock had 32% mortality, a recent single-institution observational study by Burlew et al found that pre-peritoneal packing as first-line therapy for 128 patients with hemorrhagic shock from unstable pelvic fractures was associated with mortality of only 21%, 26 challenging the notion that pre-peritoneal packing should be relegated to salvage therapy. In the present study, mortality in patients with hemorrhagic shock from pelvic hemorrhage was 27%.…”
Section: Discussionmentioning
confidence: 99%
“…A recent multicenter prospective observational study of 1,339 patients with pelvic fracture found that angioembolization and external pelvic fixation were the most common hemorrhage control techniques for arterial and venous bleeding respectively. 25 Whereas the subgroup with hemorrhagic shock had 32% mortality, a recent single-institution observational study by Burlew et al found that pre-peritoneal packing as first-line therapy for 128 patients with hemorrhagic shock from unstable pelvic fractures was associated with mortality of only 21%, 26 challenging the notion that pre-peritoneal packing should be relegated to salvage therapy. In the present study, mortality in patients with hemorrhagic shock from pelvic hemorrhage was 27%.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the pelvic ring not only acts as a marker for the high amount of kinetic energy absorbed by the body at the time of impact but may also cause significant blood loss into the retroperitoneal space from fractured bone surfaces, disruption of the pelvic venous plexus, and/or torn branches of the internal iliac arteries 3,4 . Active arterial bleeding can be managed in the hospital either non-surgically with arterial angioembolization 5 or surgically with preperitoneal pelvic packing 6 , alone or in combination with arterial angioembolization 7,8 . While several studies have shown the effectiveness of PCCDs in terms of fracture reduction [9][10][11] , data on their hemodynamic efficiency are lacking or controversial [12][13][14] .…”
mentioning
confidence: 99%
“…A presença de lesão abdominal associada, com necessidade de laparotomia exploradora (LE), é relatada entre 50% e 77,77% pelas séries que publicaram os resultados do TXP (13,18,31,37) Vários estudos (13,20,30,37,40) demonstraram melhora significativa dos parâmetros hemodinâmicos e diminuição da necessidade de transfusões sanguíneas (9,13,18,20,36,40,42) (95) . A infusão de soluções intravenosas que contenham lactato pode confundir a interpretação da sua concentração, embora seja necessária uma quantidade muito grande destas soluções para causar tal efeito (96) .…”
Section: Segmentos Corpóreosunclassified
“…O atendimento do paciente com fratura de pelve deve seguir a sequência de prioridades preconizada pelo ATLS e a presença de fratura pélvica deve ser considerada indicadora de trauma grave e múltiplo (11,20) . O tratamento possui quatro pilares: a) o diagnóstico rápido das possíveis causas de choque e fontes de sangramento, b) o controle de danos da reanimação volêmica utilizando protocolos de transfusão maciça, c) tratamento multidisciplinar da hemorragia pélvica e d) tratamento das lesões associadas.…”
unclassified
See 1 more Smart Citation